"GRUDIA ME TENUIT CULTRIX STUDIOSA MINERVAE": Textos relacionados con la estancia en Lovaina del humanista español Juan de Verzosa - Delpino González, Eduardo (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
The Latin writing Spanish humanist Juan de Verzosa (1523-1574) lived in Louvain between 1542 and 1546 and taught on Greek Language there. During these years, he established relationships with other humanists, like the Portuguese Damiâo de Goes; the Italian Girolamo Faleto and fellows Spaniards, like Fernando Ruiz de Villegas or Juan de Rojas Sarmiento. As a result of these acquaintances, some circunstantial poems (written by Verzosa or written to him) were published in different Renaissance books. In this article, I present an edition and study of these Latin texts, as a contribution to illustrate the stay of Spanish humanists in the cultural centre of Louvain in XVIth Century.